Investigation of respiratory syncytial virus in children with respiratory tract infection by real-time polymerase chain reaction - Bakır, Ayfer; Karabulut, Nuran; Alaçam, Sema; Meşe, Sevim; Yaman, Murat; Somer, Ayper; Ağaçfidan, Ali (Journal of Surgery and Medicine, 2019)
Aim: Respiratory syncytial virus (RSV) is the most common agent of respiratory tract infections (RTIs) in the early stages of life. This study aimed to investigate RSV A/B in children with RTIs by multiplex Polymerase Chain Reaction (PCR) and evaluate the distribution of RSV among age groups, concurrent co-infections, and features of its seasonal distribution. Methods: Zero to eighteen-year-old patients whose nasopharyngeal swab samples were analyzed with the pre-diagnosis of RTI between April 2015 - March 2018 were included in this cross-sectional study. RSV A/B and other viruses of the respiratory panel were investigated with the multiplex real-time PCR method. Results: Median age of 2707 patients was 1 (age range: 0-18) and 57.4% (1554) of them were male. RSV positivity was found in 14.4% (390). Prevalence of RSV in females and males were 13.6% and 15.5% respectively (P=0.16). The highest RSV rate was 18.1% in those younger than one year. Mixed infection factors were found in 5.4%, the most common ones being RSV and human rhinovirus (1.8%). RSV was mostly seen in December, followed by January and February (P<0.001). Conclusion: RSV was found in 14.4% of the pediatric patients with RTI. We found that RSV was more common under the age of 1. In this study, we determined that RSV was commonly seen in winter. Early diagnosis of RSV with real-time PCR plays a crucial role in the prevention of unnecessary use of antibiotics and nosocomial infections. It may also help to implement an effective approach to the prevention, control, and treatment of RTIs during winter when the incidence increases.